Transition-Metal-Free Cross-Coupling of Acetals and Grignard Reagents To Form Diarylmethyl Alkyl Ethers and Triarylmethanes - Qin, Yang; Liu, Sheng; Shi, Shi-Liang (Synthesis, 2023)
We herein report a transition-metal-free cross-coupling reaction of acetals and Grignard reagents. The method provides a modular preparation of diarylmethyl alkyl ethers, triarylmethanes, and 1,1-diarylalkanes that constitute the core structures of many bioactive molecules and synthetic motifs. A series of readily accessible acetals bearing aryl, alkenyl, and alkyl substituents efficiently coupled with commercially available aryl, alkyl, and allylic magnesium bromides to give the products in high yields. In addition to acyclic and cyclic acetals, ketal and orthoester also serve as viable substrates to afford sterically hindered tertiary ether and ketal respectively. A sequential difunctionalization of acetals led to the rapid synthesis of triarylmethanes and diarylalkanes.
Keywords: transition-metal-free; cross-coupling; acetals; Grignard reagents; diarylmethyl alkyl ethers; triarylmethanes